2014
DOI: 10.1111/1556-4029.12550
|View full text |Cite
|
Sign up to set email alerts
|

Driving Under the Influence of Synthetic Cannabinoid Receptor Agonist XLR‐11

Abstract: The case of a 22-year-old male Caucasian driver is presented. He was involved in a traffic collision. At the roadside, he displayed blank stare and mellow speech with a barely audible voice. A DRE found low body temperature, rigid muscle tone, normal pulse, lack of horizontal and vertical gaze nystagmus, nonconvergence of the eyes, dilated pupil size, and normal Pupillary reaction to light. A standard toxicology DUID protocol was performed on the driver's whole blood including ELISA and GC-MS drug screens with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 1 publication
(1 reference statement)
1
17
0
Order By: Relevance
“…First reports on this issue presented 7 (Musshoff et al, 2014) and 16 (Tuv et al, 2014) A c c e p t e d M a n u s c r i p t 11 Karinen et al, 2015;Lemos, 2014;Louis et al, 2014;Peterson and Couper, 2015).…”
Section: Synthetic Cannabimimetics (Scs)mentioning
confidence: 99%
“…First reports on this issue presented 7 (Musshoff et al, 2014) and 16 (Tuv et al, 2014) A c c e p t e d M a n u s c r i p t 11 Karinen et al, 2015;Lemos, 2014;Louis et al, 2014;Peterson and Couper, 2015).…”
Section: Synthetic Cannabimimetics (Scs)mentioning
confidence: 99%
“…Recent knowledge on NPS toxicodynamics demonstrates that these compounds can have a potential effect on driving ability. Several DUID case reports have already been published, often after an additional screening was performed to identify possible NPS in cases of accidents or when standard toxicological drug analyses revealed negative results …”
Section: Introductionmentioning
confidence: 99%
“…Several DUID case reports have already been published, often after an additional screening was performed to identify possible NPS in cases of accidents or when standard toxicological drug analyses revealed negative results. [13][14][15][16][17][18][19][20][21] In this article, it was our aim to estimate the NPS positivity rate in the general driving population. In addition, the prevalence of co-use of other illegal or prescription drugs was evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Four of the six compounds (UR-144, XLR-11, AKB-48, and AB-FUBINACA) have been identified in samples of synthetic cannabinoids obtained on the street (Kavanagh et al, 2013; Uchiyama et al, 2013; Strano Rossi et al, 2014). All six of the compounds have been found in blood or urine samples (or identified by verbal report) of users reporting adverse effects (Behonick et al, 2014; Gugelmann et al, 2014; Mohr et al, 2014; Strano Rossi et al, 2014), and the use of UR-144 or XLR-11 has been reported in cases of driving under the influence (Lemos, 2014; Musshoff et al, 2014). Of further concern, several of these compounds have been reported to produce significant adverse effects.…”
Section: Introductionmentioning
confidence: 99%